Minimum wage legislation: effects on levels of employment - Neumark, David (Henry Stewart Talks, 2024)
Minimum-wage legislation, Low-skilled employment, Employment level, Minimum-wage outcomes, Poverty, Inequality, Redistributive policy, Digitization, Automation